Exchange Rate implication on Raw Materials’ Import in Nigeria (1981-2015) - Dankumo, Ali Madina; Yahya, Musa; Shido-Ikwu, Sunday Benjamin; Daniel, Idowu Onisanwa (IJRDO - Journal of Social Science and Humanities Research, 2018)
There is no any self-sufficient country on this globe as all countries get involved in economic relationships through the trade of goods and services. Developing countries like Nigeria needs foreign inputs to facilitate its developmental desires. This process involves the use of different currencies, whose values can only be determined through the exchange rate. This study, therefore, used Auto Regressive Distributed Lag (ARDL) model to analyze the implication of exchange rate on raw material imports in Nigeria from 1981-2015. Augmented Dickey-Fuller (ADF) test is used to test the stationarity of each of the variable. A maximum lag of 2 is used for the model based on Schwarz information criterion (SIC). The ADF result shows that all the variables are stationary at their first difference at 1% level of significance. The short-run result shows that exchange rates have a negative and significant effect on raw material import whereas inflation shows a positive and insignificant effect on raw material import and trade openness has a negative and insignificant effect on raw material import. While in the long run, the result shows that exchange rate has a positive and significant impact on raw material import while inflation has a negative and insignificant impact on raw material import and trade openness has a positive but insignificant impact on raw material import. The paper made some policy recommendations.